2013
DOI: 10.1002/pc.22700
|View full text |Cite
|
Sign up to set email alerts
|

Cure kinetics and thermal stability of multifunctional epoxy/anhydride containing release agent and carbon fiber

Abstract: The investigations were carried out into the cure kinetics and thermal stability of multifunctional epoxy/anhydride/imidazole/release agent system (matrix) and carbon fiber reinforced matrix composite. Two experimental techniques were applied: dynamic differential scanning calorimetry (DSC) at different heating rates, and non‐isothermal thermogravimetric analysis (TGA). The results were indicated that the two‐parameter model was found to describe the cure kinetics for the matrix and the composite. The kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The analysis of curing kinetic for imide systems was performed with Kissinger and Crane methods. [25][26][27][28][29][30] According to Kissinger equation (eqn (1)), the activation energy E can be obtained from the slope of the plots of ln(b/T p 2 )…”
Section: Non-isothermal Cure Kinetics Of Imide Systemsmentioning
confidence: 99%
“…The analysis of curing kinetic for imide systems was performed with Kissinger and Crane methods. [25][26][27][28][29][30] According to Kissinger equation (eqn (1)), the activation energy E can be obtained from the slope of the plots of ln(b/T p 2 )…”
Section: Non-isothermal Cure Kinetics Of Imide Systemsmentioning
confidence: 99%
“…Afterward, the Málek approach was used to find the appropriate f (α) with the data obtained from the nonisothermal DSC measurement . Two precise functions, y (α) and z (α), were constructed; these were approximated by the following equations: y|α=|dαdtnormalexp|χ z|α=|dαdtTβnormalπ|χ where χ is the reduced activation energy ( E a / RT ) and π(χ) is the fourth‐order rational expression of the temperature integral, as follows: π|χ=χ3+18χ2+88χ+96χ4+20χ3+120χ2+240χ+120 y (α) and z (α) were normalized and plotted as a function of the conversion, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, the M alek approach was used to find the appropriate f(a) with the data obtained from the nonisothermal DSC measurement. 43,51,52 Two precise functions, y(a) and z(a), were constructed; these were approximated by the following equations:…”
Section: Surface Chemistry Of the Functionalized Mwcntsmentioning
confidence: 99%
“…Our previous studies have shown that the aminated PPTA can significantly strengthen and toughen triglycidyl‐ p ‐aminophenol (TGPAP) epoxy resin and its carbon fiber composite, and having little effect on the T g of EP 29,30 . Nowadays, in the fields of mechanical, electrical, electronics, aerospace, chemical, transportation, and construction, tetraglycidyl diamino diphenyl methane (TGDDM) epoxy resin and its carbon fiber composite are widely used because of their heat resistance and high performance 31–33 . Therefore, it is crucial to explore and investigate the reinforcing agent for TGDDM that can efficiently improve the mechanical properties and maintain the heat resistance, which has barely been reported.…”
Section: Introductionmentioning
confidence: 99%